2020
DOI: 10.1007/s00464-020-07641-1
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative and oncological outcomes following minimally invasive versus open pancreaticoduodenectomy for pancreatic duct adenocarcinoma

Abstract: Background The outcomes of minimally invasive pancreaticoduodenectomy have not been adequately compared with those of open pancreaticoduodenectomy in patients with pancreatic ductal adenocarcinoma. We performed a meta‐analysis to compare the perioperative and oncological outcomes of these two pancreaticoduodenectomy procedures specifically in patients with pancreatic ductal adenocarcinoma. Methods Before this study was initiated, a specific protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…They found that LPD was associated with longer 3-year survival, 4-year survival, and 5-year survival time, and there was no difference in 1-year survival, 2-year survival time, lymph nodes harvested, the number of positive lymph nodes, and R0 rate. The meta-analysis of Yin et al ( 9 ) covered 9,144 PDAC participants from six retrospective studies, and the meta-analysis of Sun et al ( 8 ) covered 1,377 minimally invasive pancreaticoduodenectomy (LPD and RPD) and 9,865 OPD from nine retrospective studies. They advised that LPD was associated with higher R0 rate, longer operative time, fewer blood loss, lower transfusion rate, and shorter length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…They found that LPD was associated with longer 3-year survival, 4-year survival, and 5-year survival time, and there was no difference in 1-year survival, 2-year survival time, lymph nodes harvested, the number of positive lymph nodes, and R0 rate. The meta-analysis of Yin et al ( 9 ) covered 9,144 PDAC participants from six retrospective studies, and the meta-analysis of Sun et al ( 8 ) covered 1,377 minimally invasive pancreaticoduodenectomy (LPD and RPD) and 9,865 OPD from nine retrospective studies. They advised that LPD was associated with higher R0 rate, longer operative time, fewer blood loss, lower transfusion rate, and shorter length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of minimally invasive PD on DGE development, the findings are inconclusive. National registries [ 37 ] and meta-analyses [ 38 , 39 ] were not able to detect an effect, single-center studies showed different results ( 40 , 41 ). Robotic PD was introduced in our department several years ago, but because its use does not span the whole period, we did not include minimally invasive PD into our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among these, one study focused on vessel resection; therefore, survival comparison between RAPD and open PD was not performed 13 . For patients with PDAC, a recently published meta‐analysis comparing minimally invasive PD and open PD included only one study of RAPD 14,15 . Moreover, this study included only 19 patients with PDAC in RAPD compared to open PD patients 14 .…”
Section: Discussionmentioning
confidence: 99%